2021
DOI: 10.1111/ejss.13186
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH drives poplar rhizosphere soil microbial community responses to ozone pollution and nitrogen addition

Abstract: Ground‐level ozone (O3) pollution frequently coincides with the deposition of anthropogenic nitrogen (N), and both factors can influence the structure and functionality of both above‐ and belowground ecosystems. Elevated O3 levels have been shown to adversely impact plants in many prior reports, but the interacting effects of high O3 levels and N addition on exposed plants remain to be clearly defined, and the changes in rhizosphere microbial community composition in this context have yet to be studied. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…In the current study, elevated ozone significantly altered the composition of the fungal community. Short-term ozone exposure may be a major explanatory factor for the insignificant responses of bacterial community composition to elevated ozone (Li et al, 2022). Crop type had a pronounced impact on bacterial and fungal community composition (Table S6).…”
Section: Effects Of Elevated Ozone On Soil Microbial Activity Functio...mentioning
confidence: 99%
“…In the current study, elevated ozone significantly altered the composition of the fungal community. Short-term ozone exposure may be a major explanatory factor for the insignificant responses of bacterial community composition to elevated ozone (Li et al, 2022). Crop type had a pronounced impact on bacterial and fungal community composition (Table S6).…”
Section: Effects Of Elevated Ozone On Soil Microbial Activity Functio...mentioning
confidence: 99%
“…In addition to SOM, we did not detect significant differences in soil pH between the unburned control and prescribed burn-treated plots. Soil pH typically increases following a prescribed burn treatment ( Certini, 2005 ; Bonanomi et al, 2022 ) and soil pH is a strong driver of soil microbial community composition ( Zhalnina et al, 2015 ; Parfrey, Moreau & Russell, 2018 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of SEM (Figure 7) showed that O 3 fumigation had direct impacts on pH, nutrients, and enzyme activities of poplar rhizosphere soil, while O 3 fumigation had an indirect negative impact on microbial community composition due to the changed nutrients. A study by Li et al [11] has shown that increasing O 3 indirectly affected the microbial communities of plant rhizosphere soil by increasing soil pH rather than by reducing available plant carbon sources. Therefore, the effects of O 3 on the composition and structure of microbial communities need to be further explored.…”
Section: Effects Of Ozone On Microorganisms In Rhizosphere Soilmentioning
confidence: 99%
“…From June to August 2016, ozone replaced PM 10 and PM 2.5 as the primary pollutant in the three urban agglomerations of Beijing-Tianjin-Hebei, Yangtze River Delta, and Pearl River Delta in China [3]. Many studies have found that near-surface O 3 could destroy photosynthetic pigments and damage chloroplasts in plants [4,5], change carbon metabolism [6,7], affect enzyme activities [8,9] and microbial communities [10,11], which might reduce production of crops and trees, and even lead to the degradation of forest ecosystem [12].…”
Section: Introductionmentioning
confidence: 99%